The dynamics of patient organizations in Europe - Madeleine Akrich, João Nunes, Florence Paterson, Vololona Rabeharisoa (dir.) (Presses des Mines, 2008)
Patient organizations today play a major role in the scientific, economic and political arenas. They have become the quasi-obliged partners of researchers, industrialists and political authorities. This book investigates this quite recent configuration by offering an in-depth exploration of three thematic issues: To what social and political stakes are patient organizations confronted as regards the transformation, production, circulation, and governance of knowledge? The involvement of patie...